Breast cancer with gastric metastasis in invasive lobular carcinoma: a case report and literature review - Liu, Bing; Han, Zhifei; Hu, Fangqi; Wang, Yufei; Wang, Xiaofeng; Zhang, Jiazi; Chai, Jie (Frontiers in Oncology, 2025)
Breast cancer is one of the most common malignant tumors in women. Most early-stage breast cancer does not have the typical symptoms and signs. The common metastatic sites of breast cancer are bones, lymph nodes, soft tissues, lungs, brain, liver. Cases with the gastrointestinal (GI) tract as the first site of metastasis are relatively rare. Their clinical, imaging, and gastroscopic manifestations lack specificity, making them difficult to distinguish from primary gastric cancer. A 45-year-old woman presented with a week-long history of black stools, later diagnosed as gastric metastasis from breast cancer. The patient had undergone surgery, radiotherapy, and chemotherapy 18 years prior for left invasive lobular carcinoma (ILC) of the breast. Current symptoms included black stools, hiccups, fatigue, and decreased appetite, with no nausea, fever, or chills. Gastroscopy revealed a gastric ulcer, and biopsy confirmed poorly differentiated gastric adenocarcinoma. PET-CT indicated high metabolism in the stomach but no distant metastasis. A total gastrectomy with lymph node dissection revealed tumor invasion of the serosal membrane and nerves, confirming metastatic breast cancer. Postoperative treatment and follow-up showed no recurrence or metastasis, and the patient remained stable. Gastric metastasis from breast cancer is an uncommon condition, mostly associated with invasive lobular carcinoma. Accurate diagnosis requires careful consideration of the patient’s medical history and a comprehensive approach utilizing clinical manifestations, imaging, endoscopy, histopathology, and immunohistochemistry (IHC) to minimize the risk of missed or incorrect diagnoses. Treatment remains centered on systemic therapies, including chemotherapy and endocrine therapy.